Regulating the Sea from the Shore: The Silent Clash between Indonesia’s Government Regulation No. 26 of 2023 and UNCLOS - Freidelino P.R.A. de Sousa (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2026)
This article critically repositions the precautionary principle and due diligence obligations as foundational norms in the international law of the sea that should have been operationalized in Government Regulation No. 26 of 2023, enacted as an implementing instrument of Article 56 of Law No. 32 of 2014 on Maritime Affairs. It interrogates the regulation’s underlying that whether the Government Regulation No. 26 of 2023 can be normatively harmonized with UNCLOS to ensure compliance with the precautionary principle and due diligence obligations in regulating coastal and marine spaces? In light of the legal policy of it, which reflects a utilitarian–economic rationality that legitimizes marine sediment exploitation through administrative licensing, this study argues against this such approach, primarily such regulatory logic departs from the normative architecture of UNCLOS 1982, which embeds precaution and environmental stewardship as core constraints on the exercise of sovereign rights over maritime areas. The analysis demonstrates that Government Regulation No. 26 of 2023 represents a substantive normative shift, distancing Indonesia’s coastal governance framework from both its domestic maritime legislation and its international legal commitments. This article advances the argument that a structural realignment of the regulation’s substantive content is imperative to reintegrate precaution and due diligence as binding regulatory standards. Normative harmonization is thus essential to prevent systemic incoherence between national regulatory practice and the international law of the sea.